The Importance of Instilling Aqidah Education From An Early Age - Putri, Dwi Adhinda Junaidi; Salpina, S; Maisura, M (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, 2023)
This study aims to analyze the inculcation of aqidah education in children. It is very important to instill aqidah education from an early age, so that children can understand the Oneness of Allah SWT so that when the child grows up he will grow up with a strong faith. The research method in this research is library research by analyzing various references such as journals, books and various other reading sources related to the discussion in this study. The research results obtained from this study are that aqidah education must be applied from an early age because this period is a determining period for the future. Planting aqidah education can be done in various ways, while the method recommended by Rasulullah SAW is to teach the word Allah in the early days when children start learning to speak, then continue with the sentence of monotheism, instilling a sense of love for Allah and Rasulullah SAW, in the early days of awareness, knowledge, and the ability to distinguish between good and bad, teaching the Qur'an to children, starting with short letters, then long letters, also accompanied by the habit of reading and listening to the recitation, and getting children to pray at the age of seven years.